Naar een betere startpositie op de arbeidsmarkt Onderzoek naar de aansluiting onderwijs-arbeidsmarkt voor MBO'ers met een migratieachtergrond - Bisschop, Paul (SEO Economisch Onderzoek, 2021)
MBO students with a non-Western migration background experience a less successful entry into the labor market than MBO students without a migration background. There are various explanations for the backlog, which partly lie within the sphere of influence of students, study programs and employers. MBO programs are strongly focused on the internship period in strengthening the starting position of MBO students with a non-Western migration background.